ANALYSIS ON THE TREND OF PORE PRESSURE IN WEST BARAM DELTA, MIRI, SARAWAK - MHD HANAPIAH, NURHAJEERAH (2019)
Studies of overpressure characterization are carried out in order to avoid the drilling hazard and crucial in hydrocarbon exploration and production as well as reservoir management. This research is carried out in West Baram Delta, Miri where main trend of pore pressure, causes of overpressure mechanism and overpressure generation are thoroughly investigate.